The Relationship Between Earnings Quality and Corporate Governance in the Chinese Manufacturing Industry - ZHUGE, YUEYING (2020)
Despite the increased research on earnings quality (EQ), the problems associated with financial scandal related earnings still exist. Therefore, to address these issues, stronger corporate governance (CG) is needed to reduce the possibility of earnings manipulation, improve firm performance, and enhance relationships with all stakeholders. The primary purpose of this dissertation is to examine the relationship between CG and EQ in the Chinese manufacturing industry. Eight interested CG variables were selected to reflect its effectiveness, while the level of EQ was measured by accrual earnings management and real earnings management. Descriptive statistical analysis and Pooled Ordinary Least Squares (OLS) regression were applied for 2,125 listed companies with 7,980 observations over the 2015-2019 period. The main findings of this paper include that companies with the separation of CEO and chairperson and that had received a standard unqualified auditor opinion have fewer earnings management behaviours, while companies with more frequent board meetings might engage in more earnings management activities. In addition, a higher percentage of shares held by the largest shareholders and higher executive compensation can both reduce the probability of accrual-based earnings management. In contrast, a higher proportion of independent directors and higher executive compensation motivate managers to engage in real earnings management. These obtained results provided some supportive evidence of previously introduced CG theories, especially the agency theory, because, comparatively, it better explains the occurrence of earnings management activities. These findings are expected to provide insights into improving the effectiveness of CG mechanisms and accelerating the development of the Chinese manufacturing industry with better quality. Keywords: Earnings Quality, Earnings Management, Corporate Governance, The Chinese Manufacturing Industry